2016
DOI: 10.28945/3545
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Entry Doctoral Admission Variables and Retention at a Hispanic Serving Institution

Abstract: Doctoral student retention remains a challenge in higher education with an average attrition rate of 50%. This study focuses on analyzing pre-entry variables of admission for 81 doctoral students admitted to a doctoral program in psychology to determine whether significant associations existed between specific variables in the graduated and withdrawn groups in this cohort with over 48% Hispanic doctoral student representation. Using various quantitative analyses, findings demonstrate that the variables of GPA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Other researchers have indicated that nearly 50% of the students who enroll in doctoral programs will not complete them (Ali & Kohun, 2007;Council of Graduate Schools, 2010;Young, 2005). Consequently, a disproportionate volume of research specific to doctoral programs focuses on the aftermath of student admissions rather than preadmission variables (Hoyle, 2007;Kiley, 2011;Marrero, 2016). Despite an interest in doctoral degree completion, only a few researchers have examined the role of the preadmission processes in doctoral education (e.g., Kuncel, Wee, Serafin, & Hezlett, 2010;Marrero, 2016;Rockinson-Szapkiw, Bray, & Spaulding, 2014;Young, 2008).…”
Section: Admission Criteria For Educational Leadership Doctoral Studementioning
confidence: 99%
See 3 more Smart Citations
“…Other researchers have indicated that nearly 50% of the students who enroll in doctoral programs will not complete them (Ali & Kohun, 2007;Council of Graduate Schools, 2010;Young, 2005). Consequently, a disproportionate volume of research specific to doctoral programs focuses on the aftermath of student admissions rather than preadmission variables (Hoyle, 2007;Kiley, 2011;Marrero, 2016). Despite an interest in doctoral degree completion, only a few researchers have examined the role of the preadmission processes in doctoral education (e.g., Kuncel, Wee, Serafin, & Hezlett, 2010;Marrero, 2016;Rockinson-Szapkiw, Bray, & Spaulding, 2014;Young, 2008).…”
Section: Admission Criteria For Educational Leadership Doctoral Studementioning
confidence: 99%
“…Consequently, a disproportionate volume of research specific to doctoral programs focuses on the aftermath of student admissions rather than preadmission variables (Hoyle, 2007;Kiley, 2011;Marrero, 2016). Despite an interest in doctoral degree completion, only a few researchers have examined the role of the preadmission processes in doctoral education (e.g., Kuncel, Wee, Serafin, & Hezlett, 2010;Marrero, 2016;Rockinson-Szapkiw, Bray, & Spaulding, 2014;Young, 2008). Although approximately 3,000 students of educational leadership doctoral programs graduate each year, little is known about preadmission criteria and the ability to predict doctoral student performance, particularly in education programs (Knapp, Kelly-Reid, & Ginder, 2011).…”
Section: Admission Criteria For Educational Leadership Doctoral Studementioning
confidence: 99%
See 2 more Smart Citations